(untitled) (Comprehensive Journal of Science, 2026)
This study aims to analyze contemporary trends in giftedness and academic excellence research, focusing on the evolution of theoretical frameworks, identification methods, and educational and psychological support practices for gifted students، A systematic review and thematic analysis were conducted on scientific literature published between 2015 and 2025، The study adopted a descriptive-analytical approach using thematic analysis, examining a purposive sample of fifty (50) peer-reviewed studies and academic theses published in Arabic and English, selected according to predefined inclusion and exclusion criteria، The findings reveal a clear shift from traditional single-dimensional models based on academic achievement or general intelligence toward multidimensional frameworks that integrate cognitive, emotional, motivational, and contextual factors، The results also highlight an increasing reliance on multi-criteria identification methods and comprehensive support programs that address both academic development and psychological well-being، Additionally, the analysis identifies significant research gaps, including the scarcity of longitudinal and intervention-based studies and the limited cultural representation, particularly in Arab contexts، The study emphasizes the need for integrated theoretical and practical approaches and calls for educational policies that balance academic excellence with the psychological well-being of gifted students.